Positive electrode active material, positive electrode, and rechargeable lithium battery
Patent Information
- Application Number
- CN202610436783.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-07
- Filing Date
- 2026-04-03
- Publication Date
- 2026-10-16
Smart Images

Figure CN122930898A_ABST
Abstract
Description
Technical Field
[0001] A positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery are disclosed. Background Technology
[0002] Portable information devices such as cellular phones, laptops, and smartphones use rechargeable lithium batteries, which have high energy density and are easy to carry, as their power source. High-energy-density rechargeable lithium batteries are also used as drive power sources or energy storage sources for hybrid or electric vehicles.
[0003] Various positive electrode active materials are already used in rechargeable lithium batteries. With the recent rapid increase in demand for high-capacity or high-energy-density rechargeable lithium batteries, there is a need to develop positive electrode active materials that can increase capacity while ensuring stability and enabling operation at high voltages. Summary of the Invention
[0004] This document discloses a positive electrode active material capable of providing high density, high capacity, high efficiency, and long cycle life characteristics in rechargeable lithium batteries, as well as a positive electrode including the positive electrode active material and a rechargeable lithium battery.
[0005] In some embodiments, the positive electrode active material includes: a first positive electrode active material comprising a first lithium nickel-based composite oxide in the form of secondary particles wherein a plurality of primary particles are agglomerated, wherein the primary particles have an average particle size of about 0.6 μm to about 1.05 μm as measured by electron backscatter diffraction; and a second positive electrode active material comprising a second lithium nickel-based composite oxide in the form of single particles, wherein the average particle size (D) of the secondary particles of the first positive electrode active material is... 50 The average particle size (D) of a single particle of the active material of the second positive electrode is greater than that of the active material of the second positive electrode. 50 ), wherein, based on the total amount of 100% by weight of the first positive electrode active material and the second positive electrode active material, the positive electrode active material includes about 10% to about 45% by weight of the first positive electrode active material and about 55% to about 90% by weight of the second positive electrode active material.
[0006] In some embodiments, the positive electrode includes a current collector and a layer of positive electrode active material on the current collector; wherein the layer of positive electrode active material includes the positive electrode active material.
[0007] Some example implementations provide a rechargeable lithium battery that includes the positive electrode, negative electrode, and electrolyte.
[0008] According to some embodiments, the positive electrode active material has maximized capacity, ensures long cycle life characteristics, and improves characteristics at high voltages and high-temperature storage. Rechargeable lithium batteries using the above-described positive electrode active material can exhibit high initial charge / discharge capacity and efficiency and long cycle life characteristics. Attached Figure Description
[0009] Figure 1 This is a diagram of a cylindrical rechargeable lithium battery.
[0010] Figure 2 This is a cross-sectional view of a prismatic rechargeable lithium battery.
[0011] Figure 3 and 4 A schematic exploded perspective view of a pouch-type rechargeable lithium battery.
[0012] Figure 5 This is an image of the cross-section of the first positive electrode active material according to Example 1, as observed by electron backscatter diffraction.
[0013] Figure 6 This is an image of the cross-section of the active material of the first positive electrode according to Comparative Example 3, as observed by electron backscatter diffraction. Detailed Implementation
[0014] Specific embodiments are described in detail below to enable those skilled in the art to readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the embodiments set forth herein.
[0015] The terminology used herein is for descriptive purposes only and is not intended to limit the scope of this disclosure. Unless the context clearly requires otherwise, singular expressions include plural expressions.
[0016] As used in this article, “combination of” means mixtures, laminates, complexes, copolymers, alloys, blends, reaction products, etc. of the constituent elements.
[0017] Terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0018] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc., may be exaggerated, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on said other element, or there may be intermediate elements present. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements present.
[0019] The term "layer" in this article includes not only shapes that form across the entire surface when viewed from a plan view, but also shapes that form on a portion of the surface.
[0020] The average particle size can be measured by methods known to those skilled in the art, such as by electron backscatter diffraction, by a particle size analyzer, or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating the average particle size therefrom.
[0021] "Or" is not interpreted as having an exclusive meaning. For example, "A or B" is interpreted as including A, B, A+B, etc.
[0022] "Metals" include common metals, transition metals, and metalloids (semi-metals).
[0023] Positive electrode active material
[0024] In some embodiments, the positive electrode active material includes: a first positive electrode active material comprising a first lithium nickel-based composite oxide in the form of agglomerated secondary particles of primary particles, the primary particles having an average particle size of about 0.6 μm to about 1.05 μm as measured by electron backscatter diffraction; and a second positive electrode active material comprising a second lithium nickel-based composite oxide in the form of single particles. The average particle size (D) of the secondary particles of the first positive electrode active material is... 50 The average particle size (D) of a single particle of the active material of the second positive electrode is greater than that of the active material of the second positive electrode. 50 The positive electrode active material comprises about 10 to about 45% of the first positive electrode active material and about 55 to about 90% of the second positive electrode active material, based on a total amount of 100% by weight of the first positive electrode active material and the second positive electrode active material.
[0025] In positive electrodes comprising positive electrode active materials including lithium nickel-based composite oxides, designs have been proposed to maximize capacity and achieve long cycle life characteristics by mixing large and small particles. The positive electrode can be manufactured by applying a positive electrode composition including the positive electrode active material onto a current collector and drying it, followed by compression. Positive electrodes comprising both large and small particles can suffer from problems such as large particle breakage, electrode cracking, or surface damage during the compression process. Furthermore, repeated charging and discharging of the battery can accelerate the degradation of large particles, leading to reduced cycle life characteristics. Additionally, since the number of large particles is typically designed to be greater than the number of small particles for high-density positive electrode designs, the characteristics of large particles significantly affect the characteristics of the positive electrode. Furthermore, if the primary particles of the large particles are too large, the electrochemical active surface area decreases, which reduces the efficiency of the positive electrode. Moreover, the increased strain due to volume changes during charging and discharging negatively impacts maintaining high-temperature cycle life. Furthermore, if the primary particles of the large particles are too small, the following problem arises: reduced crystallinity, which reduces the capacity of the positive electrode.
[0026] In embodiments of this disclosure, the capacity of the rechargeable lithium battery is maximized and the battery has a long cycle life by increasing the density of the positive electrode active material layer and suppressing the degradation of the positive electrode through fine control of the composition, size and mixing ratio of the positive electrode active material.
[0027] According to some embodiments, the positive electrode active material includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material includes a first lithium-nickel-based composite oxide, and the second positive electrode active material includes a second lithium-nickel-based composite oxide. The first positive electrode active material may be represented as large particles, and the second positive electrode active material may be represented as small particles. The first lithium-nickel-based composite oxide and the second lithium-nickel-based composite oxide may be the same or different.
[0028] In some embodiments, the first lithium-nickel-based composite oxide and the second lithium-nickel-based composite oxide may each be represented independently by chemical formula 1.
[0029] [Chemical Formula 1]
[0030] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1
[0031] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7, 0 ≤ z1 ≤ 0.7, 0.9 ≤ x1 + y1 + z1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 and M 2 The elements can be different and can be independently one or more of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X can be one or more of F, P, and S. In a further embodiment of Formula 1, 0.6 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.4, and 0 ≤ z1 ≤ 0.4; or 0.6 ≤ x1 ≤ 0.9, 0.1 ≤ y1 ≤ 0.4, and 0 ≤ z1 ≤ 0.1; or 0.5 ≤ x1 ≤ 0.7, 0.3 ≤ y1 ≤ 0.5, and 0 ≤ z1 ≤ 0.1; or 0.6 ≤ x1 ≤ 0.8, 0.2 ≤ y1 ≤ 0.4, and 0 ≤ z1 ≤ 0.1.
[0032] Lithium-nickel-based composite oxides can be represented, for example, by chemical formula 2 or chemical formula 3.
[0033] [Chemical Formula 2]
[0034] Li a2 Ni x2 Co y2 M 3 z2 O 2-b2 X b2
[0035] In chemical formula 2, 0.9 ≤ a² ≤ 1.2, 0.6 ≤ x² ≤ 0.99, 0.01 ≤ y² ≤ 0.4, 0 ≤ z² ≤ 0.39, 0.9 ≤ x² + y² + z² ≤ 1.1, and 0 ≤ b² ≤ 0.1, M 3 It can be one or more of the following: Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X can be one or more of F, P, and S.
[0036] [Chemical Formula 3]
[0037] Li a3 Ni x3 Co y3 M 4 z3 M 5 w3 O 2-b3 X b3
[0038] In chemical formula 3, 0.9 ≤ a³ ≤ 1.2, 0.6 ≤ x³ ≤ 0.98, 0.01 ≤ y³ ≤ 0.19, 0.01 ≤ z³ ≤ 0.39, 0 ≤ w³ ≤ 0.19, 0.9 ≤ x³ + y³ + z³ + w³ ≤ 1.1, and 0 ≤ b³ ≤ 0.1, M 4 It can be Al, Mn, or a combination thereof, M 5 It can be one or more of B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X can be one or more of F, P, and S.
[0039] The nickel content (based on 100 mol% of the total metals other than lithium) in the first lithium-nickel-based composite oxide can be greater than the nickel content (based on 100 mol% of the total metals other than lithium) in the second lithium-nickel-based composite oxide. The nickel content (based on 100 mol% of the total metals other than lithium) in the first lithium-nickel-based composite oxide and the nickel content (based on 100 mol% of the total metals other than lithium) in the second lithium-nickel-based composite oxide can each independently be about 50 mol% to about 70 mol%, for example, about 50 mol% to about 65 mol%, about 55 mol% to about 65 mol%, or about 60 mol% to about 65 mol%. In the first lithium-nickel-based composite oxide, the nickel content based on 100 mol% of the total metals excluding lithium can be greater than or equal to about 50 mol%, for example, about 50 mol% to about 70 mol%, about 50 mol% to about 65 mol%, about 55 mol% to about 65 mol%, about 60 mol% to about 80 mol%, about 65 mol% to about 80 mol%, about 60 mol% to about 75 mol%, about 60 mol% to about 70 mol%, or about 60 mol% to about 65 mol%. In the second lithium-nickel-based composite oxide, the nickel content based on 100 mol% of the total metals excluding lithium can be greater than or equal to about 50 mol%, for example, about 50 mol% to about 70 mol%, about 55 mol% to about 70 mol%, about 50 mol% to about 65 mol%, about 55 mol% to about 65 mol%, about 50 mol% to about 65 mol%, about 55 mol% to about 60 mol%, or about 60 mol% to about 65 mol%. Furthermore, the ratio of the molar nickel content (excluding lithium) of 100 mol% of the total metals in the first lithium-nickel-based composite oxide to the molar nickel content (excluding lithium) of 100 mol% of the total metals in the second lithium-nickel-based composite oxide can be from about 1.05 to about 1.3, for example from about 1.05 to about 1.2, or from about 1.05 to about 1.1. When the amounts of nickel in the first and second lithium-nickel-based composite oxides are within these ranges, high capacity can be achieved in rechargeable lithium batteries while improving structural stability, reducing side reactions with the electrolyte, and achieving long cycle life characteristics.
[0040] The first positive electrode active material, including the first lithium-nickel-based composite oxide, can be in the form of secondary particles formed by the aggregation of multiple primary particles. The secondary particles can be spherical, ellipsoidal, polyhedral, or irregularly shaped. The primary particles forming the secondary particles can be spherical, ellipsoidal, plate-like, or a combination thereof.
[0041] The second positive electrode active material, including the second lithium-nickel-based composite oxide, can be in the form of single particles, and these single particles can have spherical, ellipsoidal, polyhedral, or irregular shapes. The single particles exist independently without grain boundaries, are composed of a single particle, and can be single particles, monolithic structures, integral structures, or non-agglomerated particles, wherein the particles do not aggregate but exist as independent phases in terms of morphology. A single particle can be represented as a monolithic particle or a single crystal, for example, as a single crystal. Single particles can exist independently or aggregate together. For example, 2 to 10 single particles can aggregate and contact each other.
[0042] The average particle size (D) of the secondary particles of the first positive electrode active material 50 The average particle size (D) can be from about 8 μm to about 20 μm, and can be, for example, from about 10 μm to about 18 μm or from about 12 μm to about 16 μm. Here, the average particle size (D) 50 The particle size distribution can be obtained by using a particle size analyzer (PSA) on the first positive electrode active material, and taking the diameter of the particles representing 50% of the cumulative volume of the particle size distribution as the average particle size.
[0043] The average particle size (D) of a single particle of the second positive electrode active material 50 The average particle size (D) can be from about 1 μm to about 8 μm, for example, from about 1.5 μm to about 7 μm, or from about 2 μm to about 6 μm. Here, the average particle size (D) 50 The particle size distribution can be obtained by using a particle size analyzer to obtain the particle size distribution of the second positive electrode active material, and the diameter of the particles with a cumulative volume of 50% in the particle size distribution is taken as the average particle size.
[0044] Particle size analysis of secondary particles of the first positive electrode active material and single particles of the second positive electrode active material can be performed, for example, using a laser diffractometer such as the LS13320 (Beckmann Coulter). As particle size analysis conditions, the pump speed can be 55%, ultrasonic dispersion can be performed at 40 kHz for 30 seconds, the run length can be 60 seconds, the refractive index can be 1.6, the e-factor (extinction factor) can be 1.00, the sample amount can be 0.20 g, and the dispersant added to the sample can be 1 ml of 10% sodium hexametaphosphate. 50 It refers to the size of particles that have a cumulative volume of 50% in the particle size distribution.
[0045] In some embodiments, such as by electron backscatter diffraction, the average particle size (particle size) of the primary particles forming the secondary particles of the first positive electrode active material can be about 0.6 μm to about 1.05 μm, for example about 0.65 μm to about 1.05 μm, about 0.68 μm to about 1.03 μm, about 0.69 μm to about 1.02 μm, about 0.65 μm to about 1.0 μm, about 0.6 μm to about 0.9 μm, about 0.65 μm to about 0.9 μm, about 0.6 μm to about 0.8 μm, or about 0.65 μm to about 0.8 μm. The aspect ratio of the primary particles forming the secondary particles of the first positive electrode active material, as measured by electron backscatter diffraction, can be about 2.7 to about 3.3, for example, about 2.7 to about 3.2, about 2.8 to about 3.2, about 2.8 to about 3.3, about 2.8 to about 3.1, about 2.9 to about 3.2, about 2.9 to about 3.1, or about 3.0 to about 3.1. Here, the average primary particle size and aspect ratio can be measured by electron backscatter diffraction (EBSD) analysis. The EBSD measurement device can be, for example, the Symmetry S3 EBSD from Oxford, and the sample can be ion milled (ground) using a CP (cross-section polisher, ArBlade5000, Hitachi). EBSD can be measured using an e-flash HR EBSD detector from Bruker at an accelerating voltage of 15 keV and a current of 13 nA. Primary particles can refer to grains. The average particle size of the primary particles refers to the average particle size of a single particle as measured by EBSD, and the aspect ratio of the primary particles can refer to the aspect ratio of a single particle as measured by EBSD. When the average particle size and aspect ratio of the primary particles forming the first positive electrode active material are within the above ranges, the electrochemical active surface area increases, thereby improving the efficiency of the positive electrode and minimizing strain due to volume changes during charging and discharging. This enables the maintenance of high-temperature cycle life and increased capacity due to high crystallinity.
[0046] D of the positive electrode active material 50 It can be from about 1 μm to about 20 μm, for example, from about 1.5 μm to about 10 μm, or from about 2 μm to about 5 μm. Here, D 50 The particle size distribution of the total positive electrode active material, including the first positive electrode active material and the second positive electrode active material, can be obtained by using a particle size analyzer, and the diameter of the particles with a cumulative volume of 50% in the particle size distribution can be taken as the average particle size.
[0047] In some example embodiments, the BET (Brunauer-Emmett-Teller) specific surface area of the positive electrode active material can be approximately 0.6 m². 2 / g to approximately 0.9 m 2 / g, for example, about 0.6 m 2 / g to approximately 0.85 m 2 / g, approximately 0.65 m 2 / g to approximately 0.85 m 2 / g or approximately 0.7 m 2 / g to approximately 0.85 m 2 / g. Here, the BET specific surface area can be the BET specific surface area of the total positive electrode active material, including the first and second positive electrode active materials, measured by nitrogen adsorption using a specific surface area measuring device. When the specific surface area of the positive electrode active material is within the above range, the electrochemical active surface area increases, thereby improving the efficiency of the positive electrode.
[0048] In some embodiments, based on the total amount of 100% by weight of the first and second positive electrode active materials, the first positive electrode active material may be included in an amount of about 10% to about 45% by weight, for example, about 15% to about 40% by weight, about 20% to about 40% by weight, about 20% to about 35% by weight, or about 20% to about 30% by weight, and the second positive electrode active material may be included in an amount of about 55% to about 90% by weight, for example, about 60% to about 85% by weight, about 60% to about 80% by weight, about 65% to about 80% by weight, or about 70% to about 80% by weight. When the ratio of the first and second positive electrode active materials is such that the positive electrode active material can have a high capacity, the density of the positive electrode active material layer can be improved, and the positive electrode active material can have a high energy density.
[0049] The particle (disc) density of the positive electrode active material can be from about 3.0 g / cc to about 3.8 g / cc, for example from about 3.1 g / cc to about 3.7 g / cc, from about 3.2 g / cc to about 3.6 g / cc, or from about 3.3 g / cc to about 3.4 g / cc. Positive electrodes with such high particle density can have high capacity and energy density.
[0050] positive electrode
[0051] In some embodiments, the positive electrode includes a positive electrode current collector and a layer of positive electrode active material on the current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other positive electrode active materials. Furthermore, the positive electrode active material layer may further include a binder, a conductive material, or a combination thereof.
[0052] In some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm².2 Approximately 40 mg / cm 2 For example, approximately 10 mg / cm 2 Approximately 35 mg / cm 2 or about 10 mg / cm 2 Approximately 30 mg / cm 2 The density of the positive electrode active material layer in the compressed final positive electrode can be from about 3.2 g / cc to about 3.7 g / cc, for example from about 3.3 g / cc to about 3.6 g / cc or from about 3.4 g / cc to about 3.5 g / cc. When the positive electrode active material according to the embodiments of this disclosure is applied, it is advantageous to achieve such a loading level and density of the positive electrode active material layer, and such a range can provide a high-capacity, high-energy-density rechargeable lithium battery.
[0053] The thickness of the positive electrode active material layer can be from about 5 μm to about 300 μm, for example from about 10 μm to about 250 μm, or from about 20 μm to about 200 μm. When the thickness of the positive electrode active material layer is within these ranges, high-capacity and high-energy-density batteries can be achieved.
[0054] adhesive
[0055] Binders improve the adhesion properties between the active material particles of the positive electrode and with the current collector. Examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers (ethylene oxide-containing polymers), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resins, (meth)acrylate resins, polyester resins, and nylon. However, this disclosure is not limited to these examples.
[0056] conductive materials
[0057] This includes conductive materials to provide electrode conductivity, and any electrically conductive material that can be used in the battery without causing undesirable chemical changes. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0058] Based on a 100% by weight positive electrode active material layer, the amount of binder and conductive material can be from about 0.5% by weight to about 5% by weight.
[0059] The current collector may be formed from an aluminum thin film, but this disclosure is not limited thereto.
[0060] Rechargeable lithium batteries
[0061] Some embodiments provide a rechargeable lithium battery that includes the above-described positive electrode, negative electrode, and electrolyte. As an example, a rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte solution.
[0062] Depending on their shape, rechargeable lithium batteries can be cylindrical, prismatic, pouch-shaped, coin-shaped, etc. Figures 1 to 4 To illustrate a schematic diagram of a rechargeable lithium battery according to some embodiments, wherein Figure 1 It is a cylindrical battery. Figure 2 It is a prismatic battery, and Figure 3 and 4 It is a pouch-shaped battery. (See reference) Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50, such as... Figure 1 As shown. Figure 2 As shown, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and 4 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, namely a positive electrode terminal 71 and a negative electrode terminal 72, which form an electrical path for leading the current generated in the electrode assembly 40 to the outside of the battery.
[0063] negative electrode
[0064] The negative electrode may include a current collector and a negative electrode active material layer on the current collector, and the negative electrode active material layer may include a negative electrode active material and may further include a binder, a conductive material or a combination thereof.
[0065] Negative electrode active material
[0066] The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials that can be doped / dedoped with lithium, or transition metal oxides.
[0067] The material capable of reversibly intercalating / deintercalating lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as the carbon-based negative electrode active material. The crystalline carbon may be irregular, or flake-like, scaly, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, and the like.
[0068] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0069] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material.
[0070] The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy, or a combination thereof. In the formula Si-Q, Q is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (other than Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof. The Sn-based negative electrode active material may be Sn, SnO₂, a Sn alloy, or a combination thereof.
[0071] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter (D of the silicon-carbon composite particles 50 ) may be, for example, from about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0072] The silicon-carbon composite may further include crystalline carbon. The silicon-carbon composite may include, for example, a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon or hard carbon, a mesophase pitch carbonized product, and calcined coke.
[0073] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be about 50 wt% to about 90 wt%. In addition, based on 100 wt% of the silicon-carbon composite, when the composite includes silicon, amorphous carbon and crystalline carbon, the amount of silicon may be about 10 wt% to about 50 wt%, the amount of crystalline carbon may be about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be about 20 wt% to about 40 wt%.
[0074] The thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle diameter (D of the silicon particles (primary particles) 50 ) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0<x≤2). The atomic content ratio of Si:O indicating the oxidation degree may be about 99:1 to about 33:67. As used herein, when no additional definition is provided, the average particle diameter (D 50 ) refers to the diameter of particles at which the cumulative volume in the particle size distribution is about 50% by volume.
[0075] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be a weight ratio of about 1:99 to about 90:10.
[0076] adhesive
[0077] The binder is used to adhere the negative electrode active material particles to each other, and is also used to adhere the negative electrode active material to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0078] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.
[0079] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.
[0080] When an aqueous binder is used as the negative electrode binder, it may further include a cellulose compound capable of imparting viscosity. As a cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be Na, K, or Li.
[0081] Dry adhesives can be polymeric materials that can be turned into fibers, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0082] conductive materials
[0083] This includes conductive materials to provide electrode conductivity, and any electrically conductive material that can be used in the battery without causing undesirable chemical changes. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0084] Based on a 100% by weight negative electrode active material layer, the amount of negative electrode active material may be from about 95% by weight to about 99.5% by weight, and based on the 100% by weight negative electrode active material layer, the amount of binder may be from about 0.5% by weight to about 5% by weight. The negative electrode active material layer may include about 90% by weight to about 99% by weight of negative electrode active material, about 0.5% by weight to about 5% by weight of binder, and about 0.5% by weight to about 5% by weight of conductive material.
[0085] current collector
[0086] The current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or alloys thereof, and may be in the form of foil, sheet or foam.
[0087] The thickness of the current collector can be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.
[0088] electrolytes
[0089] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.
[0090] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.
[0091] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, and caprolactone. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Additionally, ketone solvents may include cyclohexanone. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups, etc.); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.
[0092] Non-aqueous organic solvents can be used alone or in mixtures of two or more types. When two or more types are used in mixtures, the mixing ratio can be appropriately adjusted according to the desired battery performance, as is known to those skilled in the art.
[0093] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0094] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0095] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery cycle life.
[0096] Examples of ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0097] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include at least one selected from: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0098] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. When the concentration of lithium salt is in this range, the electrolyte solution has suitable ionic conductivity and viscosity, and therefore excellent performance can be achieved and lithium ions can move efficiently.
[0099] diaphragm
[0100] Depending on the type of rechargeable lithium battery, a separator may be present between the positive and negative electrodes. The separator may include multilayer films of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, etc.
[0101] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.
[0102] The porous substrate may be a polymer film formed from polymers selected from: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene ether; cyclic olefin copolymers; polyphenylene sulfide; polyethylene naphthalate; glass fiber; Teflon®; and polytetrafluoroethylene; or copolymers or mixtures of two or more thereof.
[0103] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0104] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, wherein the second structural unit includes at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylsulfonic acid or a salt thereof.
[0105] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. However, this disclosure is not limited to these examples. The average particle size (D) of the inorganic particles... 50 The wavelength can be from about 1 nm to about 2000 nm, for example from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0106] Organic and inorganic materials can be mixed in a single coating. In another embodiment, a coating comprising organic materials and a coating comprising inorganic materials can be stacked.
[0107] The coating thickness can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm or from about 1 μm to about 5 μm.
[0108] The following describes embodiments and comparative examples of the present disclosure. However, the present disclosure is not limited to the following embodiments.
[0109] Example 1
[0110] 1. Preparation of positive electrode active material
[0111] Ni 0.65 Co 0.05 Mn 0.30 (OH)₂ and LiOH were mixed to have a molar ratio of (Ni+Co+Mn):Li = 1:1. The mixture was then heat-treated at 880°C for 8 hours under an oxygen atmosphere to prepare particles with an average size (D) of 12 μm. 50 LiNi in the form of secondary particles 0.65 Co 0.05 Mn 0.30 The composition of O2 includes a first positive electrode active material consisting of a first lithium nickel-based composite oxide.
[0112] Figure 5The image shows a cross-sectional image of the first positive electrode active material as detected by electron backscatter diffraction. In this case, the first positive electrode active material has a primary particle size of 0.697 μm and a primary particle aspect ratio of 3.05.
[0113] Ni 0.60 Co 0.10 Mn 0.30 (OH)₂ and LiOH were mixed to have a molar ratio of (Ni + Co + Mn):Li = 1:1. The mixture was then heat-treated at 1000°C for 8 hours under an oxygen atmosphere to obtain LiNi. 0.60 Co 0.10 Mn 0.30 The product was composed of O2. The product was pulverized using a needle mill to prepare a particle size (D) with an average particle size of 4 μm. 50 The second positive electrode active material is a single-particle form containing a second lithium nickel-based composite oxide.
[0114] The first positive electrode active material and the second positive electrode active material are mixed in a weight ratio of 4:6 to prepare the positive electrode active material.
[0115] 2. Manufacturing of rechargeable lithium battery cells
[0116] A slurry for the positive electrode active material was prepared by mixing 98.5 wt% of the positive electrode active material, 1.0 wt% of the polyvinylidene fluoride binder, and 0.5 wt% of the carbon nanotube conductive material in N-methyl-2-pyrrolidone (NMP) solvent. The slurry was coated onto an aluminum foil current collector, then dried and compressed to form the positive electrode.
[0117] A negative electrode active material slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene-butadiene rubber in an aqueous solvent. The negative electrode active material slurry was coated onto a copper foil current collector, dried, and compressed to form a negative electrode.
[0118] Subsequently, a polytetrafluoroethylene (PTFE) separator is used. Furthermore, rechargeable lithium-ion battery cells are prepared using a conventional method with an electrolyte solution prepared by dissolving 1 M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a 3:7 volume ratio.
[0119] Example 2
[0120] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were mixed in a weight ratio of 3:7 to prepare the positive electrode active material.
[0121] Example 3
[0122] The positive electrode active material and the rechargeable lithium battery cell were prepared in essentially the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were mixed in a weight ratio of 2:8 to prepare the positive electrode active material.
[0123] Example 4
[0124] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: Ni was used... 0.65 Co 0.05 Mn 0.30 A mixture of (OH)2 and LiOH was heat-treated at 910 °C for 8 hours to prepare a first positive electrode active material with a primary particle size of 1.012 μm and a primary particle aspect ratio of 3.16.
[0125] Example 5
[0126] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were mixed at a weight ratio of 1:9 to prepare the positive electrode active material.
[0127] Example 6
[0128] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were mixed in a weight ratio of 4.5:5.5 to prepare the positive electrode active material.
[0129] Comparative Example 1
[0130] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: Ni was used... 0.65 Co 0.05 Mn 0.30 A mixture of (OH)2 and LiOH was heat-treated at 910 °C for 16 hours to prepare a first positive electrode active material having a primary particle size of 1.214 μm and a primary particle aspect ratio of 3.45. In the preparation of the positive electrode active material, the first positive electrode active material and the second positive electrode active material were mixed in a weight ratio of 5:5.
[0131] Comparative Example 2
[0132] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: Ni was used... 0.65 Co 0.05 Mn 0.30 A mixture of (OH)2 and LiOH was heat-treated at 840°C for 8 hours to prepare a first positive electrode active material having a primary particle size of 0.462 μm and a primary particle aspect ratio of 2.47. In the preparation of the positive electrode active material, the first positive electrode active material and the second positive electrode active material were mixed at a weight ratio of 7:3.
[0133] Comparative Example 3
[0134] Ni 0.75 Mn 0.23 Al 0.02 (OH)₂ and LiOH were mixed to have a molar ratio of (Ni+Mn+Al):Li = 1:1. The mixture was then heat-treated at 845°C for 8 hours under an oxygen atmosphere to prepare particles with an average size (D) of 12 μm. 50 LiNi in the form of secondary particles 0.75 Mn 0.23 Al 0.02 The first positive electrode active material containing a first lithium nickel-based composite oxide is composed of O2. Figure 6 The image shows a cross-sectional image of the first positive electrode active material as detected by electron backscatter diffraction. The first positive electrode active material has a primary particle size of 0.697 μm and a primary particle aspect ratio of 2.02.
[0135] The second positive electrode active material was prepared in the same manner as in Example 1, and the positive electrode active material and rechargeable lithium battery cell were made in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were mixed in a weight ratio of 7:3.
[0136] Comparative Example 4
[0137] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 3, except that: in the preparation of the positive electrode active material, Ni was... 0.75 Mn 0.23 Al 0.02 A mixture of (OH)2 and LiOH was heat-treated at 870 °C for 8 hours to prepare a first positive electrode active material with a primary particle size of 1.081 μm and a primary particle aspect ratio of 2.18.
[0138] Comparative Example 5
[0139] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 3, except that: in the preparation of the positive electrode active material, Ni was... 0.75 Mn 0.23 Al 0.02 A mixture of (OH)2 and LiOH was heat-treated at 880 °C for 8 hours to prepare a first positive electrode active material with a primary particle size of 1.234 μm and a primary particle aspect ratio of 2.21.
[0140] Comparative Example 6
[0141] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 3, except that: in the preparation of the positive electrode active material, Ni was... 0.75 Mn 0.23 Al 0.02 A mixture of (OH)2 and LiOH was heat-treated at 820 °C for 8 hours to prepare a first positive electrode active material with a primary particle size of 0.403 μm and a primary particle aspect ratio of 1.82.
[0142] Comparative Example 7
[0143] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 3, except that: in the preparation of the positive electrode active material, Ni was... 0.75 Mn 0.23 Al 0.02 A mixture of (OH)2 and LiOH was heat-treated at 830°C for 8 hours to prepare a first positive electrode active material having a primary particle size of 0.549 μm and a primary particle aspect ratio of 1.92, and the first positive electrode active material and the second positive electrode active material were mixed at a weight ratio of 6:4.
[0144] Comparative Example 8
[0145] The positive electrode active material and rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 3, except that: in the preparation of the positive electrode active material, Ni was... 0.75 Mn 0.23 Al 0.02 A mixture of (OH)2 and LiOH was heat-treated at 820°C for 8 hours to prepare a first positive electrode active material having a primary particle size of 0.403 μm and a primary particle aspect ratio of 1.82, and the first positive electrode active material and the second positive electrode active material were mixed at a weight ratio of 3:7.
[0146] Comparative Example 9
[0147] The positive electrode active material and the rechargeable lithium battery cell were prepared in the same manner as in Comparative Example 8, except that: in the preparation of the positive electrode active material, Ni was... 0.75 Mn 0.23 Al 0.02 A mixture of (OH)2 and LiOH was heat-treated at 870 °C for 8 hours to prepare a first positive electrode active material with a primary particle size of 1.081 μm and a primary particle aspect ratio of 2.18.
[0148] The composition of the first lithium-nickel-based composite oxide, the primary particle size and aspect ratio of the first positive electrode active material, the composition of the second lithium-nickel-based composite oxide, and the weight ratio of the first positive electrode active material and the second positive electrode active material are shown in Table 1.
[0149] Electron backscatter diffraction (EBSD) analysis of the primary particle size and aspect ratio of the active material of the first positive electrode was performed using an Oxford Symmetry S3 EBSD as the EBSD measurement instrument, with the sample subjected to ion milling using a CP (ArBlade 5000, Hitachi). EBSD measurements were performed using an e-flash HR EBSD detector manufactured by Bruker Ltd. at an accelerating voltage of 15 keV and a current of 13 nA.
[0150] Table 1
[0151]
[0152] Evaluation 1: Specific surface area
[0153] The BET specific surface area of the positive electrode active materials of the examples and comparative examples was measured, and the results are shown in Table 2. The BET specific surface area was measured using a specific surface area measuring device (HM model-1208 manufactured by Mounttech) using the nitrogen adsorption method. Specifically, approximately 0.3 g of each positive electrode active material sample was heated in a pre-processor at 300°C for 1 hour under a nitrogen atmosphere and further pre-treated in the specific surface area measuring device at 300°C for 15 minutes, then cooled to the temperature of liquid nitrogen and saturated by adsorption with a gas containing 30% nitrogen and 70% He. Subsequently, the sample was heated to room temperature to measure the amount of desorbed gas, which was used to calculate its specific surface area using the conventional BET method.
[0154] Evaluation 2: Initial charge / discharge capacity and efficiency
[0155] The rechargeable lithium battery cells of the examples and comparative examples were initially charged and discharged at 25°C with a constant current of 0.2 C to an upper limit voltage of 4.3 V, and then charged with a constant voltage to 0.05 C and discharged with a constant voltage of 0.2 C to a cutoff voltage of 3.0 V.
[0156] Table 2 shows the initial charge capacity (0.2 C charging) and initial discharge capacity (0.2 C discharging), as well as the ratio of the latter to the former as calculated for efficiency.
[0157] Evaluation 3: High-temperature cycle life
[0158] Following the initial charge / discharge of Evaluation 2, the individual cells were charged and discharged at 1.0 C for 50 or more cycles at 45°C within a voltage range of 3.0 V to 4.3 V to calculate the ratio of the discharge capacity at the 50th cycle to the initial discharge capacity. The results, presented as high-temperature cycle life, are shown in Table 2.
[0159] Table 2
[0160]
[0161] Referring to Table 2, the examples were demonstrated to exhibit high initial discharge capacity and initial charge / discharge efficiency, as well as excellent high-temperature cycle life characteristics. In particular, the positive electrode active material prepared according to Example 3, using a first positive electrode active material having a primary particle size of 0.697 μm and a primary particle aspect ratio of 3.05, and mixing the first and second positive electrode active materials at a weight ratio of 2:8, exhibited the highest initial charge / discharge efficiency and excellent high-temperature cycle life characteristics.
[0162] On the other hand, compared with the examples, Comparative Examples 1 to 7, which exclude 55% to 90% of the second positive electrode active material based on 100% by weight of the total amount of the first positive electrode active material and the second positive electrode active material, and Comparative Examples 2 and 4 to 9, whose first positive electrode active material does not have a primary particle size of 0.60 μm to 1.05 μm, were shown to exhibit lower initial discharge capacity and initial charge / discharge efficiency as well as poor high-temperature cycle life characteristics.
[0163] Evaluation 4: Density of Aggregates (Flakes)
[0164] The particle density of the positive electrode active material was measured using the following method. 3 grams of the positive electrode active material were placed in a mold (area: 1.298 cm²). 2 The mold rod is then slowly inserted into the mold body. The mold assembly is placed in a hydraulic press and pressed for 30 seconds under a pressure of 4 tons (metric tons) to measure the height, which is used to measure the agglomerate density.
[0165] Example 2, in which a first lithium nickel-based composite oxide and a second lithium nickel-based composite oxide were mixed at a weight ratio of 3:7, was measured to have a pellet density of 3.39 g / cc.
[0166] On the other hand, when the first lithium-nickel-based composite oxide and the second lithium-nickel-based composite oxide from Example 2 were mixed at a weight ratio of 1:9, the agglomerate density was measured to be 3.18 g / cc. When the first lithium-nickel-based composite oxide from Example 2 was used alone, the agglomerate density was measured to be 3.12 g / cc. And when the second lithium-nickel-based composite oxide from Example 2 was used alone, the agglomerate density was measured to be 3.00 g / cc. Therefore, when the first lithium-nickel-based composite oxide and the second lithium-nickel-based composite oxide were mixed at a weight ratio of 3:7 according to Example 2, a high agglomerate density was achieved, thereby providing high capacity and energy density.
[0167] While this disclosure has been described with respect to what are considered practical exemplary embodiments, it will be understood that this disclosure is not limited to the disclosed embodiments. Rather, this disclosure includes various modifications and equivalent arrangements.
Claims
1. Positive electrode active material, including: A first positive electrode active material comprising a first lithium-nickel-based composite oxide and in the form of secondary particles aggregated as primary particles, said primary particles having an average particle size of 0.6 μm to 1.05 μm as measured by electron backscatter diffraction; and The second positive electrode active material includes a second lithium-nickel-based composite oxide and is in the form of single particles; The average particle size D of the secondary particles of the first positive electrode active material 50 The average particle size D of the single particles is greater than that of the second positive electrode active material. 50 ,and Wherein, based on the total amount of 100% by weight of the first positive electrode active material and the second positive electrode active material, the positive electrode active material includes 10 to 45% by weight of the first positive electrode active material and 55 to 90% by weight of the second positive electrode active material.
2. The positive electrode active material according to claim 1, wherein the first lithium-nickel-based composite oxide and the second lithium-nickel-based composite oxide are each independently represented by the following: Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 Where 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, 0≤z1≤0.7, 0.9≤x1+y1+z1≤1.1, and 0≤b1≤0.1, M 1 and M 2 The elements are different and each is one or more of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is one or more of F, P, and S.
3. The positive electrode active material according to claim 1, wherein the nickel content of the first lithium nickel-based composite oxide based on 100 mol% of the total metals other than lithium in the first lithium nickel-based composite oxide is greater than the nickel content of the second lithium nickel-based composite oxide based on 100 mol% of the total metals other than lithium in the second lithium nickel-based composite oxide.
4. The positive electrode active material according to claim 1, wherein the nickel content of the first lithium nickel-based composite oxide based on 100 mol% of the total metals other than lithium in the first lithium nickel-based composite oxide and the nickel content of the second lithium nickel-based composite oxide based on 100 mol% of the total metals other than lithium in the second lithium nickel-based composite oxide are each independently from 50 mol% to 70 mol%.
5. The positive electrode active material according to claim 1, wherein the nickel content, based on 100 mol% of the total metals other than lithium in the first lithium-nickel-based composite oxide, is 60 mol% to 70 mol%, and The nickel content, based on 100 mol%, of the total metals other than lithium in the second lithium-nickel-based composite oxide is 55 mol% to 65 mol%.
6. The positive electrode active material according to claim 1, wherein the ratio of the molar nickel content in the first lithium nickel-based composite oxide based on 100 mol% of the total metals other than lithium in the first lithium nickel-based composite oxide to the molar nickel content in the second lithium nickel-based composite oxide based on 100 mol% of the total metals other than lithium in the second lithium nickel-based composite oxide is 1.05 to 1.
3.
7. The positive electrode active material according to claim 1, wherein the average particle size D of the secondary particles of the first positive electrode active material is... 50 The thickness ranges from 8 μm to 20 μm.
8. The positive electrode active material according to claim 1, wherein the average particle size D of the single particles of the second positive electrode active material is... 50 The range is from 1 μm to 8 μm.
9. The positive electrode active material according to claim 1, wherein the average particle size of the primary particles of the first positive electrode active material, as measured by electron backscatter diffraction, is 0.65 μm to 0.8 μm.
10. The positive electrode active material according to claim 1, wherein the aspect ratio of the primary particles of the first positive electrode active material, as measured by electron backscatter diffraction, is 2.7 to 3.
3.
11. The positive electrode active material according to claim 1, wherein the aspect ratio of the primary particles of the first positive electrode active material, as measured by electron backscatter diffraction, is 3.0 to 3.
1.
12. The positive electrode active material according to claim 1, wherein the BET specific surface area of the positive electrode active material is 0.6 m². 2 / g to 0.9 m 2 / g.
13. The positive electrode active material according to claim 1, wherein, Based on a total amount of 100% by weight of the first positive electrode active material and the second positive electrode active material, the positive electrode active material comprises 20 to 30% by weight of the first positive electrode active material and 70 to 80% by weight of the second positive electrode active material.
14. The positive electrode active material according to claim 1, wherein the particle density of the positive electrode active material is from 3.0 g / cc to 3.8 g / cc.
15. Positive electrode, including: current collector; and The positive electrode active material layer on the current collector, The positive electrode active material layer thereunder comprises the positive electrode active material according to any one of claims 1 to 14.
16. The positive electrode according to claim 15, wherein the density of the positive electrode active material layer is from 3.2 g / cc to 3.7 g / cc.
17. The positive electrode according to claim 15, wherein the loading level of the positive electrode active material layer is 10 mg / cm³. 2 Up to 40 mg / cm 2 .
18. A rechargeable lithium battery, comprising: The positive electrode according to any one of claims 15 to 17; negative electrode; and Electrolytes.